READINESS TO LEARN: PRINCIPLES. CONTRIBUTING FACTORS AND HOW IT AFFECTS LEARNING - Agustiani, Indah Windra Dwie; Gumartifa, Asti Gumartifa; Yaman, Herasni Yaman (English Community Journal, 2021)
This study attempts to inform definition of learning  readiness,  the principle of readiness, factors contributing to readiness to learn and how readiness affects learning.  This study  is theory-based research or library research.This study used  secondary data.  The technique used for collecting the data is literature study. This study concludes  that the principles of readiness are not only affected  by one’s physical development  but also his/ her  mental development since they are closely interrelated.  Moreover, the suitability of the learning experiences  that will be given or the existing (prior) experiences become crucial  to result  in learning readiness and simultaneously  , and the adaptation process of basic readiness for certain activities is considered  as a natural thing when  it is in the formation period at the time of development .Factors contributing to readiness to learn are  maturation ,Intelligence, and motivation and readiness can generate active self directed learner, improve learning outcome/achievements.grow responsibility in learning ,and influence students’ activeness in learning.